Effect of Biochar-amended Organic and Inorganic Manures on Growth and Yield of Okra (Abelmoschus esculentus (L.) Moench) - Dahal, Anuja; Jaishi, Ajay; Ghimire, Subash Babu; Chaulagain, Pushpa; Koirala, Soma; Karki, Sristi; Kharal, Salon (Nepal Journal of Botany, 2025)
The cultivation of okra in the Terai region primarily relies on chemical fertilizers, which degrade microbial activity and causes nutrient imbalances, ultimately affecting the growth and yield of okra. Replacing synthetic chemical inputs with biochar (BC) and organic manures can enhance soil microbiota and crop productivity. The field experiment was conducted in Ramdhuni, Sunsari, Nepal during April –July, 2023 to evaluate the effects of BC combined with various organic and inorganic manures on growth and yield of okra. The experiment was conducted using a randomized complete block design (RCBD) with seven treatments: (200 kg Nha-1)-BC + farmyard manure (FYM), BC + vermicompost (VC), BC + poultry manure (PM), BC + goat manure (GM), BC + pig manure (PiM), BC + chemical fertilizer (NPK), and control—with each treatment replicated thrice. The yield and yield attributing characters significantly improved with biochar amended organic manures. BC+PM yielded the highest plant height (78.72 cm), number of branches (4.4), number of leaves (71.53), average fruit weight (16.42 g), and yield (19.89 Mtha-1). Compared to BC+NPK, BC+PM showed a greater increase in plant height (12.1%), number of branches (19.9%), fruit weight (21.0%) and yield (47.7%). Hence, integrating BC with PM could be an ideal treatment to reduce the effect of chemical fertilizer and maximize the productivity of okra in Nepal.